THE INFLUENCE OF THE STUDENTS PERCEPTIONS UPON COMPLETION FACILITIES LEARNING AND TEACHERS PEDAGOGIC COMPETENCE TOWARD ECONOMICS LEARNING ACHIEVEMENT - Puspita, Fitriyah (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2019)
This research aimed at analyzing the relationship of the influence of the student’s perceptions upon completion facilities learning and teacher’s pedagogic competence toward economics learning achievement. The population was swasta Senior High School’s students in Jakarta Utara. The sample taken by random sampling technique, involved 60 students. The instruments were in the forms of questioners and tests, the data were analyzed using multiple regression. The findings showed that : 1) Students’s perceptions upon completion facilities learning and teacher’s pedagogic competence had significant simultaneous impact on economics learning achievement. 2) Students’s perceptions upon completion facilities learning had significant simultaneous impact on economics learning achievement. 3) Teacher’s pedagogic competence had significant simultaneous impact on economics learning achievement.